Proline Accumulation Influenced by Osmotic Stress in Arbuscular Mycorrhizal Symbiotic Plants - Chun, Se Chul; Paramasivan, Manivannan; Chandrasekaran, Murugesan (Frontiers in Microbiology, 2018)
Salinity and drought are the major osmotic stress limitations that affect plant growth and crop yield in agriculture worldwide. The alternative response mediated by plants in response to salinity and drought are principally proline accumulation which regulates stress combat strategies owing to sustainable production in the realm of agricultural production even under severe stress. Symbiotic and soil associated arbuscular mycorrhizal fungi (AMF) are regarded as efficient biofertilizers in several crops under these stresses. Summarily AMF is renowned for effective scavengers of free radicals in soil thereby increasing soil parameters optimal for plant growth. AMF contribute to augment host plant tolerance to stress specifically salinity and drought. Mycorrhizal colonization positively regulates root uptake of available nutrients and enhance growth even when bestowed by water constraints which has contributory roles due to proline accumulation providing several intriguing research on AMF symbiosis pertaining to plant productivity and yield. Mycorrhizal plants and their non-mycorrhizal counterparts show varied expression pattern regarding proline amass. Hence, the precise role of proline with respect to stress tolerance and equivocal mechanisms involved in evasion of osmotic stress has not been extensively reviewed earlier. Further molecular forecasting in this arena is still an underexploited research field. This review comprehensively addresses the observable facts pertaining to proline accumulation upon AMF association and adherence relevant to stress tolerance and host plant efficiency and efficacy.